Symbol of Males and Females as Social Actors in Naguib Mahfouz’s Midaq Alley: A CDA Study - Majed Numan Alkhudari (Al-Qanṭara, 2022)
This paper has aimed to investigate representation of gender roles in Naguib Mahfouz's Midaq Alley, a novel originally written in Arabic, in terms of critical discourse analysis by applying Fairclough's (2001) three-dimensional model as well as drawing onVan Leeuwen's (2008) representation of social actors. The purpose of the study is firstly to find out which of the two genders has been more frequently portrayed as the primary social actor in the text; and, secondly, to unveil the ideological orientations behind certain gender-related linguistic choices in the discourse of the novel –that is, by analyzing the text on the basis of linguistic instances like male/female proper names, male/female honorifics, genders’ fitness in order of appearance in the text or in mixed-gender dialogues, appraising lexical items describing characters, and characters ‘physical identification. The findings of the analysis of the text revealed that the dominant discourse in Midaq Alley is mainly male-oriented in almost all of the genderrelated instances under investigation